Sosialisasi dan Pelatihan Literasi Digital untuk Meningkatkan Pengetahuan dan Inovasi Produk Unggulan Masyarakat Desa Poleng Kabupaten Sragen - Jazimatul Husna; Liliek Budiastuti Wiratmo; Imam Setyawan; Sri Indrahti; Siti Susanti; Nur Laili Mardhiyani; Arifa Rachma Febriyani (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2023)
This article discusses community service activities in Poleng Village, Gesi District, and Sragen Regency which focus on socialization and digital literacy training in an effort to increase knowledge and develop community superior product innovations. This service uses a Participatory Action Research (PAR) approach. The aims of this service is to motivate the people of Poleng to optimize their potential and increase innovation in regional superior products. This service answers the challenges of an increasingly sophisticated digital era and realizes the importance of empowering rural communities to explore their own potential and develop regional superior product innovations so as to increase the competitiveness and economic value of community products. Digital literacy socialization and training using the